Edukasi Pendidikan Agama Islam dalam Pemanfaatan Sumber-Sumber Elektronik pada Siswa Madrasah Ibtidaiyah - Amirah Mawardi (Departement of Mathematics Education, 2023)
This study aims to measure the utilization of technology in Islamic religious education in Madrasah Ibtidaiyah and its impact on students' religious understanding in the digital era. This study uses a Library Research approach as the main method to explore the information and data needed to answer the author's research problems. Islamic educational apps, religious websites, e-books, learning videos and online platforms have helped make religious learning more engaging and interactive. However, the research also revealed challenges related to maintaining the integrity of Islamic teachings, with the importance of monitoring electronic sources used in learning. In addition, the study suggests the need for teacher training in integrating technology into learning, as well as continuous evaluation of the effectiveness of using technology in Islamic religious education. Understanding digital ethics is also considered important in preparing students as responsible users in the online world. Thus, this study provides insights into the role of technology in Islamic religious education in the digital era, highlights the potentials and challenges, and offers suggestions for the development of religious education relevant to current technological developments. Keywords: Islamic religious education, technology age, electronic resources, madrasah ibtidaiyah